The Investigation on L1 Adaptive Control of the Tilt-Rotor Aircraft - Quanlong Chen; Shanyong Zhao; Ke Lu; Senkui Lu; Chunsheng Liu; Renliang Chen (International Journal of Aerospace Engineering)
Considering the uncertainty of the flight dynamics model of the tilt-rotor aircraft in different flight modes, an L1 adaptive controller for full flight modes control system of tilt-rotor aircraft is designed. Taking advantage of the separation of robustness and adaptive design of the L1 adaptive controller, adaptive gain, and low-pass filter are designed to achieve the desired control performance and meet the requirements of flight quality. The simulations of XV-15 tilt-rotor aircraft in helicopter mode and airplane mode are carried out. Then, the simulation of conversion mode is further carried out. The results show that the tilt-rotor aircraft can track the reference signal well under the L1 control system. In addition, the changes of states as well as controls in conversion mode flight are quite smooth which is very meaningful for engineering application.